Regenerasi Petani Melalui Pengembangan Minat Pemuda pada Kegiatan KRPL di Kecamatan Sukaraja Kabupaten Bogor - Dea Refika Nita; Oeng Anwarudin; Nazaruddin Nazaruddin (Jurnal Penyuluhan Pertanian, 2020)
Farmer regeneration is an effort to maintain and increase the number of farmers who have decreased. One of the programs to attract young generation in agriculture is Sustainable Food House Areas (SFHA) activities. The purposes of this study are to describe the level of youth interest, analyse factors that decide the interest, and formulate some strategies for developing youth interest in SFHA activities. This study was conducted in Sukatani, Sukaraja Sub-district, Bogor Regency in April – June 2020. This study used 50 peoples which determined using simple random sampling technique. The variables consist of individual characteristics, external factors, and youth interest in SFHA activities. Data analysis that used in this study is a descriptive analysis, correlation Rank Spearman analysis, and SWOT analysis. The results showed 52% of youth respondents had a high interest in SFHA activities. The factors that decide youth interest in SFHA activity are ICT access, cosmopolitan behavior, motivation, and some external factors. The strategies that can be undertaken to develop youth interest in SFHA activities are external factors support (family support, agricultural extension, community support and natural resources) to overcome the weaknesses (ICT access and cosmopolitan). Efforts that can be made are information media supply as a reference for youth generation in both of printed or electronic media, and actively conducting training and agricultural extension as a form of SFHA development.